279 Evaluation of the NRC (2012) model in estimating standard maintenance metabolizable energy requirement of PIC sows during mid-gestation. (30th November 2020) - Knauer, Mark; Purvis, Jerry; Lu, Ning; Orlando, Uislei; Vier, Carine; Cast, Wayne
Abstract: The objective was to evaluate the NRC (2012) model in predicting standard maintenance metabolizable energy (MEm ) of PIC sows during mid-gestation. A total of 201 PIC Camborough sows (parity 1 to 10) were randomly assigned to 1 of 4 treatments in a complete randomized design between day 36 and 46 post-breeding. Treatments consisted of feeding sows with daily feed allowances to meet 80, 90, 100 or 110% of MEm calculated as MEm, kcal/day = 100 × (body weight) 0.75 . A common corn-soybean meal-based diet with 3, 302 kcal of ME/kg and 0.61% standardized ileal digestible lysine was fed for 28 days. Sow body weight (BW) and sow body condition caliper score (CS) were captured at day 0, 14 and 28. Data were analyzed with PROC GLM of SAS with sow as experimental unit. Average sow parity and feed allowance were 4.2 and 1.79 kg/day, respectively. Average sow BW and sow CS at day 0, 14 and 28 were 234, 233 and 242 kg and 14.9, 14.9 and 14.8, respectively. Increasing feed allowances to meet 80 to 110% of MEm requirement increased (linear, P< 0.01) average daily gain (ADG; 0.100, 0.259, 0.417 and 0.440 kg/d, respectively). The estimated regression equation was ADG, kg/day = -0.83 + 1.193 × MEm, estimating the MEm to maintain BW was below 80% of NRC (2012) estimate. Caliper score change (CSC) increased (linear, P< 0.01) with increasing feed allowances to meet 80 to 110% of MEm requirement (-0.78, -0.26, 0.13, and 0.35, respectively). The estimated regression equation was CSC = -3.73 + 3.78 × MEm, estimating the MEm to maintain CS at 98.7% of NRC (2012) estimate. In summary, results showed that the MEm to maintain BW and CS for PIC sows during mid-gestation was below 80% and at 98.7%, respectively, of NRC (2012) estimated requirement.